Screening of central auditory processing disorder in elementary school students in the Municipality of Lages, State of Santa Catarina, Brazil (Research, Society and Development, 2024)
Central Auditory Processing Disorder (CAPD) is a deficit in the neural processing of the auditory stimulus and may coexist or be associated with changes in language development and/or neurological conditions. Changes in this processing can lead to impairments in academic performance, language delay, difficulty in properly understanding what is said and learning difficulties, which can often be confused with different childhood pathologies. Objective: This study aimed to apply the Scale of Auditory Behaviors (SAB) questionnaire to children between 10 and 11 years old in a municipal school in Lages, state of Santa Catarina, Brazil, to identify possible children with CAPD. Methods: The questionnaire was completed by parents or guardians after signing the Informed Consent Form. It presents a proposal for a cross-sectional descriptive study, with a quantitative approach of a descriptive and exploratory nature. Results: The research involved 34 children from the 5th and 6th grade of elementary school. Among the children assessed, 5 (14.71%) presented a final score indicating a formal assessment of central auditory processing and 3 (8.82%) with values indicative of central auditory processing disorder, requiring investigation and long-term follow-up. Conclusion: The results, although limited by the sample, suggest that some participants would require additional assessment. Therefore, the relevance of future research with more participants and joint hearing tests is emphasized for greater population knowledge, identification and treatment of CAPD.